Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
The exponential decay formula is:
[tex]y=a(1-r)^t[/tex]where y is the final cost, a is the initial cost, r is the annual decreasing rate (as a decimal), and t is the time in years.
Substituting with a = $60, r = 0.09, and t = 3 years, we get:
[tex]\begin{gathered} y=60\cdot(1-0.09)^3 \\ y=60\cdot(0.91)^3 \\ y=60\cdot0.75 \\ y=45.21 \end{gathered}[/tex]It will cost $45.21 in 3 years
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.